2006
DOI: 10.1097/01.aud.0000202288.21315.bd
|View full text |Cite
|
Sign up to set email alerts
|

Neural Representation of Amplified Speech Sounds

Abstract: Speech-evoked cortical potentials can be recorded reliably in individuals during hearing aid use. A better understanding of how amplification (and device settings) affects neural response patterns is still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 49 publications
7
114
2
3
Order By: Relevance
“…Some authors have studied the effect of intensity by means of interfacing with a hearing aid. A study showed that speech evoked a cortical response in normal-hearing individuals with and without amplification and found no significant effect of amplification (gain) in latency or amplitude [20] . In a previous study [17] , intensity function in hearing impaired elderly in aided conditionswas investigated by varying the intensity of the pure tones through a hearing aid, and it was reported that a larger amplitude at P2 only in the aided condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have studied the effect of intensity by means of interfacing with a hearing aid. A study showed that speech evoked a cortical response in normal-hearing individuals with and without amplification and found no significant effect of amplification (gain) in latency or amplitude [20] . In a previous study [17] , intensity function in hearing impaired elderly in aided conditionswas investigated by varying the intensity of the pure tones through a hearing aid, and it was reported that a larger amplitude at P2 only in the aided condition.…”
Section: Introductionmentioning
confidence: 99%
“…CAEP differences between speech stimuli are an indication of different underlying neural representations of speech sounds and suggest that the information needed to differentiate the stimuli is available to the listener. There has been increasing interest in the use of cortical potentials to investigate the neural encoding of speech [20] . However, the influence of various parameters of speech stimulus on ALLR is less studied, especially stimulus intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Natural speech was used as the stimulus because LLRs for natural speech show remarkable stability between recordings from the same individual. Given this stability, any significant alteration in morphology would likely reflect changes in neural activation to speech and not simply random variability [23] . Most auditory-evoked responses are onset responses triggered by the leading edge as well as the first few tens of milliseconds of the stimulus envelope, for which there is some integration of sound energy.…”
Section: Stimuli For Recording Llrsmentioning
confidence: 99%
“…Cortical auditory evoked potentials (CAEPs) are noninvasive electrophysiological measures of central auditory system function that may help to determine how hearing aid signal processing is affecting neural encoding and resulting perception (Tremblay, Billings, Friesen, & Souza, 2006). To be specific, P1-N1-P2 CAEPs are sometimes used clinically to estimate hearing thresholds and is therefore a potential tool for measuring the neural representation and threshold of amplified sound (for a review see Martin, Tremblay, & Korczak, 2008).…”
mentioning
confidence: 99%